Short-Term PE Generation Processes in the Soils of a Farmer Plots Network in the Madagascar Highlands: Actors and Drivers - Kanto Razanamalala; Tantely Razafimbelo; Pierre-Alain Maron; Lionel Ranjard; Nicolas Chemidlin Prévost-Bouré; Samuel Dequiedt; Thierry Becquer; Jean Trap; Eric Blanchart; Laetitia Bernard (Microbiology Research, 2023)
Carbon sequestration in agricultural soils, through the accumulation of high-quality organic matter, represents great potential to mitigate climate change and simultaneously improve soil fertility. Such a challenge is particularly important and relevant in developing tropical countries like Madagascar, where soil carbon storage is vulnerable to climatic variations and where fertilization is generally applied through amendments in organic matter of various origins. The priming effect (PE) is considered here as the stimulation of the mineralization of soil organic matter (SOM) by a supply of fresh organic matter (FOM). PE results from different microbial processes driven by specific biotic and abiotic parameters. Depending on the processes involved, it has been suggested that PE could either counteract SOM accumulation or promote it. The objective of the present study was to explore the relationships between certain agricultural practices (type of crop, quality of fertilization, association with trees), the potential intensity of PE, as well as several abiotic (texture, quantity and quality SOM, nutrient enrichment) a1nd biotic (biomass and phylogenetic composition of microbial communities) factors which have been proposed in the literature as specific determinants of the different PE generation mechanisms. The soils for this study come from a network of farms in a commune in the Highlands of Madagascar. The PE, generated by a supply of 13C-enriched wheat straw, could not directly correlate with agricultural treatments. However, several indirect correlations could be found via several specific abiotic and microbial determinants that are discussed in terms of soil fertility restoration.